Enhancing urban traffic flow with Arduino Traffic Management System / Aidid Zamri - Zamri, Aidid (2024)
This report presents the information and designs of an Enhancing Urban Traffic Flow with Arduino Traffic Management System by using an Arduino Mega 2560, to optimize the traffic flow and enhance the overall road safety. The objectives of the project are to build a prototype of Enhancing Urban Traffic Flow with Arduino Traffic Management System and to display the real-time traffic data and traffic light timings on an LCD display. The aim of this report is to design a Enhancing Urban Traffic Flow with Arduino Traffic Management System by using an Arduino Mega 2560. The methodology includes combining the controller that utilizes a network of sensors, and communication devices to gather real-time data on traffic patterns, vehicles, and pedestrian movements as the inputs for Arduino Mega, where the sensors used such as infrared sensors for the pedestrians before they cross the zebra-line on the road and ultrasonic sensors, mainly use to detect the presence of vehicles on the road during the red light of the traffic light is on. As for the outputs, the components are LED, buzzer, and LCD display. Simulation results shows the timing of the traffic lights to change colours. The importance of this project is in its contribution to notifying or give alertness to the people on the road and creating the traffic lights for further improvements in traffic lights.